Relações inter-regionais e intersetoriais na economia brasileira: uma aplicação de insumo-produto - Francisco Constantino Crocomo; Joaquim Jose Martins Guilhoto (Economia Aplicada, 1998)
This paper presents the study of the interregional economic structure in Brazil; this was accomplished by building an interregional input-output model. The study presents as main findings the identification of key sectors in the five regions researched. The Southeast region shows the greatest independence while the South and Northeast, according to the analysis done using the various selected methods, alternate themselves as the second most dynamic region in the Brazilian economy, followed by the Middle-West and North regions. One interesting point that is worth mentioning is the strenght of the economic structure in the Northeast region as well as the dynamic relations between this and the North region. The significant differences among all the regions demonstrate the need to reorganize the development plans in a nation with such continental dimensions.